Shade guardian: enhanced curtain automation system - Zulfikri, Ahmad Irfan; Hairuddin, Muhammad Asraf; Norhadi, Adriana Nabilah; Hamizol, Adam Muhaimin (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The Shade Guardian: Enhanced Curtain Automation System is a revolutionary smart home device that automates curtain movement while integrating advanced lighting, security, and information display features. The system utilizes a Light Dependent Resistor (LDR) to detect changes in ambient light, enabling automatic curtain adjustments to optimize natural lighting. It features an ESP32 microcontroller for wireless connectivity, allowing users to control curtains and receive notifications on their smartphones. Additional features include an LED lighting system that activates automatically in low-light conditions, a buzzer that functions as a wake-up alarm or alert for weather changes, and a Real-Time Clock (RTC) with an LCD display to provide real-time updates on the current time and weather conditions. Designed to improve energy efficiency, security, and convenience, this multi-functional system caters to households, offices, and hospitality spaces. Its unique combination of automation, smart control, and real-time information display distinguishes it from traditional curtain systems. The commercialization prospects are promising, with potential applications in smart homes, commercial buildings, and eldercare facilities. By addressing the growing demand for energy-efficient, multi-functional smart home devices, the Shade Guardian is poised to become a key player in the home automation market